Analisis Putusan Mahkamah Agung No 23 P/HUM/2024 Terhadap PKPU No 9 Tahun 2020 Tentang Syarat Minimal Usia Calon Kepala Daerah dalam Perspektif Fiqh Siyasah - Satria Bambang Gempita; Irwansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this article is to clarify the minimum requirements for regional head candidates referred to in the decision of the Supreme Court of the Republic of Indonesia No. 23 P/HUM/2024 and to find out the judge's considerations in resolving cases from the Fiqh Siyasah perspective. The writing method uses a normative approach and the data collection technique uses library research. This research is descriptive and aims at problem-solution. Based on the analysis of this article, it was found that the Supreme Court Decision No. 23 P/HUM/2024 has the potential for injustice and legal uncertainty in regional elections because it is likely not fulfilled at the time of nomination. Based on the legal implications, the decision has the potential to increase disputes in regional head elections.